International Standards in Public Participation in Financing Oil and Gas Pipelines: The Transparency of Risk Management Measures and Emergency Response Plans - E. Nickel (Society for Mining, Metallurgy & Exploration, 2005)
"Bi- and multilateral banks as well as export credit agencies in the OECD countries, but also numerous commercial banks, last year committed themselves to compliance with the World Bank’s standards. These environmental and social guidelines, also known as the Safeguard Policies, are the strictest international standards in the area of financing of major investment projects. The Safeguard Policies are procedural and quality guidelines by means of which socially and environmentally relevant impacts can be taken into account in the planning and implementation phase of a project. Objectives of the Bank Safeguard Policies are to ensure that environmental and social issues are evaluated in decision-making, to reduce and manage risk of projects and programs, and to provide a mechanism for consultation and disclosure of information. They are often referred to as the "10+1 Safeguard Policies," since ten of the guidelines address environmentally and socially relevant issues, while one guideline is exclusively concerned with public participation ("Public Disclosure"). In the presentation, the transparency of risk management measures and emergency response plans in pipeline projects will be discussed as an indicator of sustainability. The discussion is to be carried out on the basis of the results of an evaluation of several major pipeline projects, which have been financed at least in part by multilateral banks over the past few years. The controversies surrounding some of these projects due environmentally and socially relevant impairments connected with the investments have also been addressed by the Extractive Industry Report of the World Bank. Pipeline construction was the investment type chosen for the examination to be presented here, since pipelines frequently start in remote, unspoiled regions, and their routes often cross various natural zones and areas with various social structures. The question of safety during construction and operation of the line is always central to these projects; not only for the responsible authorities but also for other societal groups involved, such as environmental associations."